The Influence Of Teachers' Interpersonal Communication Competence On The Learning Satisfaction Of Generation Z Students - Ahmad Rais Habib (PT Maju Malaqbi Makkarana, 2026)
This quantitative study examines the influence of teachers’ interpersonal communication competence on the learning satisfaction of Generation Z students in Indonesia in the digital era. Employing an explanatory research design, this study used Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data collected from 50 students selected through purposive sampling. The findings indicate that teachers’ interpersonal communication competence has a positive, strong, and statistically significant effect on students’ learning satisfaction (β = 0.745, t = 6.440, p < 0.001). The model explains 55.5% of the variance in learning satisfaction, indicating a substantial explanatory power. In addition, the effect size value (f² = 1.247) demonstrates that interpersonal communication competence has a large practical contribution to students’ satisfaction with the learning process. The most prominent dimensions of teacher communication behavior are supportiveness and equality, reflected in teachers’ ability to act as approachable facilitators, provide timely and constructive feedback, and avoid rigid one-way communication patterns. These findings suggest that interpersonal communication remains essential in digital learning contexts, particularly for Generation Z students who expect responsive, inclusive, and interactive learning environments. Therefore, schools should strengthen teachers’ interpersonal and digital communication skills through continuous professional development programs to improve the quality, stability, and effectiveness of teaching and learning.